Three new sesquiterpene lactones from Carpesium abrotanoides. (October 2018) - Hu, Qiao-Ling; Wu, Pei-Qian; Liu, Ying-Hong; Qi, Feng-Ming; Yu, Chun-Xue; Zhao, Ye; Yu, Yi-Fan; Fei, Dong-Qing; Zhang, Zhan-Xin
Graphical abstract: A new eudesmane lactone (1 ) and two new carabrane lactones (2 and3 ) were isolated from the whole plant of Carpesium abrotanoides. Highlights: Three new sesquiterpene lactones were isolated from the whole plant of Carpesium abrotanoides . Their structures were established by extensive spectroscopic methods and X-ray diffraction analyses. Compound2 showed cytotoxic activity against HL-60 cells. Abstract: Three new sesquiterpene lactones, 5 α -hydroxy-4 α, 15-epoxy-11 α H-eudesman-12, 8 β -olide (1 ), carabrol-4- O -palmitate (2 ) and carabrol-4- O -linoleate (3 ), along with five known ones, were isolated from the whole plant of Carpesium abrotanoides. The structures of new compounds were determined by extensive spectroscopic analysis, and compound1 was also elucidated by X-ray single-crystal diffraction analysis. The cytotoxic activities of these new compounds against human leukemia cells HL-60 and human breast cancer cells MCF-7 were also evaluated by MTS method.